AKUNTABILITAS PENGELOLAAN LAPORA AKUNTABILITAS PENGELOLAAN LAPORAN KEUANGAN DI BUMDES MASKUMAMBANG - manto, Birson Durmanto; Erniwati, Erniwati (PT Naureen Digital Education, 2025)
This research aims to identify the ability of BUMDes in accountable financial management in Maskumambang BUMDes. The financial reports prepared by BUMDes Maskumambang are still simple, arranged neatly, transaction records are entered in detail. Insufficient knowledge of accounting can cause inaccuracies in financial reports which create obstacles in managing BUMDes finances. This study was obtained through interviews with administrators who are responsible for managing BUMDes financial reports and production. The collected data was reduced and analyzed again to draw conclusions using data triangulation analysis techniques. The results of the research stated that there were several obstacles experienced by BUMDes Maskumambang, namely in determining product prices and the prepared financial reports did not follow standard accounting criteria. Apart from that, there are work programs that have not been implemented which have resulted in delays in reporting financial statements because they have not been able to provide appropriate information. So it can be stated that the management of financial reports is considered less accountable for those who need it. Based on this research, it is hoped that it can become an evaluation tool for Maskumambang BUMDes, besides that it can be used as material for scientific studies to increase insight into the accountability of financial report management in BUMDes.